Improved earth : prairie space as modern artefact, 1869-1944 - Bantjes, Rod (CEL - Canadian Publishers Collection., 2005)
"Improved Earth is a history of the making of 'abstract spaces of modernity' in the setting of the Canadian prairies, particularly rural Saskatchewan, from 1869 to 1944. Rod Bantjes demonstrates how three interrelated projects - state formation, agrarian class formation, and the transformation of the environment - were conceived in spatial terms and employed competing visions of spatial possibility." "Bantjes proposes that the prairies be thought of as a site of modernity, and makes a case for viewing prairie farmers as 'modernists' who took an active role in transforming their world." "The first systematic treatment of the spatial dimensions of the colonization of the prairie west, Improved Earth is a unique and thorough study certain to provoke new debate about the way space and time are imagined."--Jacket